THE EFFECT OF HARMFUL AND FAVORABLE GAS AND CHEMICAL CONTENT EMITTED BY MUD VOLCANO TO ENVIRONMENT - Muhammad Burhannudinnur; Rosmalia Dita Nugraheni; Astri Rinanti (Universitas Trisakti, 2020)
The recent eruption of Kesongo mud volcano (MV) that occurred in 28August 2020 in Blora, Central Java was a common natural phenomenon.MV eruption occurred periodically depending on the recharge fluid systemthat interconnected to a geothermal system and hydrocarbon reservoir.During the eruption, methane and CO2 gas were emitted to theatmosphere together with rocks, muds and fluids flowing from the fractureand fault system of MV. The extruded materials could be harmful andbeneficial for the affected ecosystem. Aims: This study aimed to addressthe potential impact of the extruded mud volcano materials to theenvironment. Methodology and Results: An attempt was carried out byinvestigating gas and fluid content of every mud volcano morphology in theselected 11 areas of Kradenan, Central Java and Sidoarjo, East Java. The pristine fluids and gas of MV were sampled for chemical and toxiccompound observation. Gas composition and type was observed using gaschromatography. The result shows that methane gas content ranges from0.06 to 67.6 mol%., while the CO2 content ranges from 0.21 to 79.9 mol%.Methane gas exhibits thermogenic gas that associated with hydrocarbongeneration. Conclusion, significance and impact study: The chemicalcompound of fluids indicates high Boron (B) content above 0.5 ppm whichhas harmful effect for crops and human health, but some compounds ofCa, Na, K, Mg present as essential elements for soil nutrient. According tothe methane flux and chemical compound emitted by mud volcano, thisstudy contributes to a management practice to restore and conserve the global ecosystem.